The Age of Auden : Postwar Poetry and the American Scene. - Wasley, Aidan (Princeton University Press, 2011)
W.H. Auden's emigration from England to the United States in 1939 marked more than a turning point in his own life and work--it changed the course of American poetry itself. The Age of Auden takes, for the first time, the full measure of Auden's influence on American poetry. Combining a broad survey of Auden's midcentury U.S. cultural presence with an account of his dramatic impact on a wide range of younger American poets--from Allen Ginsberg to Sylvia Plath--the book offers a new history of postwar American poetry. For Auden, facing private crisis and global catastrophe, moving to the United States became, in the famous words of his first American poem, a new "way of happening."